Genetic Effects of the Schizophrenia-Related Gene DTNBP1 in Temporal Lobe Epilepsy - Tao, Hua; Zhou, Xu; Chen, Jun; Zhou, Haihong; Huang, Lidan; Cai, Yujie; Fu, Jiawu; Liu, Zhou; Chen, Yanyan; Sun, Chaowen; Zhao, Bin; Zhong, Wangtao; et al. (Frontiers in Genetics, 2021)
Recent studies have reported patients who concurrently exhibit conditions of epilepsy and schizophrenia, indicating certain shared pathologies between them. This study aimed to investigate the genetic effects of the schizophrenia-related gene DTNBP1 in temporal lobe epilepsy (TLE). A total of 496 TLE patients and 528 healthy individuals were successfully genotyped for six DTNBP1 polymorphisms (rs760665, rs1011313, rs2619528, rs2619522, rs909706 and rs2619538). The frequency of the TT genotype at rs909706 T>C was lower in TLE patients than in normal controls in the initial cohort (cohort 1), which was confirmed in an independent cohort (cohort 2). However, the intronic T allele failed to be in linkage disequilibrium (LD) with any functional variations nearby; thus, together with the CCAC and TCAT haplotypes (rs1011313-rs2619528-rs2619522-rs909706) observed in the study, this allele only acts as a protective factor against susceptibility to TLE. Meanwhile, a novo mutant allele rs2619538 T>A was exclusively observed in TLE patients, and a dual-luciferase assay revealed that the mutant allele was increased by approximately 22% in the DTNBP2 promoter compared with the wild-type allele. Together with the trend of increasing DTNBP1 expression in epilepsy patients and animal models in this study, these are the first findings to demonstrate the genetic association of DTNBP1 with TLE. Heterozygous mutation of rs2619538 T>A likely promotes DTNBP1 expression and facilitates subsequent processes in epilepsy pathologies. Thus, the role of DTNBP1 in TLE deserves further exploration in the future.